Changes in computed tomography values of mandibular condyle and temporomandibular joint disc position after sagittal split ramus osteotomy. Issue 7 (September 2015) - Ueki, Koichiro; Yoshizawa, Kunio; Moroi, Akinori; Iguchi, Ran; Kosaka, Akihiko; Ikawa, Hiroumi; Saida, Yuriko; Hotta, Asami; Tsutsui, Takamitsu
Abstract Purpose The purpose of this study was to evaluate change in computed tomography (CT) value of condyle and temporomandibular joint (TMJ) disc position after sagittal split ramus osteotomy (SSRO) setback surgery, retrospectively. Subjects and methods The subjects were 76 patients (152 condyles) who underwent bilateral SSRO setback surgery. They were divided into 2 groups (43 symmetric patients and 33 asymmetric patients). CT values (pixel values) of 5 sites of the condyle and condylar width, length, horizontal angle were measured pre-operatively and 1 year post-operatively. Disc position was classified as anterior disc displacement, anterior type, fully covered type and posterior type, preoperatively and postoperatively using magnetic resonance imaging (MRI). Results In maximum CT value at the center of the condyle, post-operative value was significantly lower than pre-operative value bilaterally (Deviation side: P = 0.0003, Non-deviation side: P = 0.0003) in asymmetry group. In minimum CT value at the center of the condyle, the post-operative value was significantly lower than the pre-operative value bilaterally (Deviation side: P = 0.0309, Non-deviation side: P = 0.0004) in the symmetry group. With regard to maximum CT value at the lateral site of the condyle in the deviation side, the value for the anterior disc displacement group was significantly larger than that of the posterior type pre-operatively (P = 0.0123). CT value of the anterior disc displacement group was significantly larger than those of some other areas pre- and post-operatively (P < 0.05). Conclusion This study suggested that CT value of condylar bone changes after 1 year in SSRO and anterior disc displacement may partially affect the CT value of the condyle in the TMJ in mandibular prognathism patients.